The Evolving Role of Nurse Leadership in the Fight for Health Equity - Azar, Kristen M.J. (Nurse leader, 2021)
Devastating disparities in COVID-19 infection and outcomes among socioeconomically marginalized groups have resulted in a public outcry to address longstanding societal inequities that have contributed to the present situation. Nurse leaders have an opportunity and an obligation in this moment to lend their skills as scientists, innovators, advocates, and educators to lead in these efforts, advancing health equity for all.